Community acceptability of public health measures during the coronavirus pandemic in Malawi: a cross-sectional survey of knowledge, attitudes, and practices - Ronald Chitatanga; Hussein H. Twabi; Clara Sambani; Collins Mitambo (AOSIS, 2023)
Background. The knowledge, attitudes, and practices (KAP) of people during the coronavirus pandemic are pivotal to the uptake of recommended preventative strategies. Objective. This paper describes the Malawian KAP related to coronavirus and associated public health measures. Methods. This was a multi-site cross-sectional survey where data was collected through personal one-on-one interviews in nine Malawian districts over 3 weeks (5-25 October 2020). 521 participants (18 years) were enrolled to answer a questionnaire. Results. We found that all respondents were aware of the ongoing coronavirus pandemic with the majority using the Radio. 75% of participants displayed knowledge of all key symptoms of coronavirus disease (cough, fever, and shortness of breath) and additionally, the majority of participants (97%) knew enough to take some sort of intervention (calling a hotline or visiting the nearest hospital) if they developed symptoms. Participants also demonstrated a high perception of the risk of coronavirus, where 60% believed to be susceptible to the coronavirus under the current preventative measures, and 50% believed they would die from the infection. Communities displayed a high perceived effectiveness of all preventative measures, with "hand hygiene using soap and water" being perceived as effective by the majority of respondents. Although the majority of the participants (80%) were willing to self-isolate at home, various barriers to home isolation were raised which would ultimately influence their ability to do so. Conclusions. Baseline community psychosocial and behavioral information which influence the adoption of public health measures in Malawi has been highlighted alongside recommendations for best practices.